Police Obstacles in Revealing the Crime of Disposing of Babies - Titik Mokoagow; Lisnawaty W. Badu; Suwitno Yutye Imran (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to know and analyze what factors hinder the police in uncovering the crime of disposal of babies in Bone Bolango and to find out what the police are trying to prevent the crime of disposal of babies in the jurisdiction of the Tapa Police. This type of research is empirical research. The results showed that the role of the police in uncovering the crime of disposal of babies in the Tapa Sector Police, the investigation process was still stopped because the police experienced factors that hindered the police in uncovering the crime of disposal of babies. These factors were internal factors consisting of a lack of members and sources. Human Resources, lack of evidence, and difficulty in determining suspects, Then there are also external factors, namely the lack of public awareness. Then, in this case, the police made efforts to prevent the crime of disposal of babies in the jurisdiction of the Tapa Police by conducting patrols, counseling and outreach activities in the community.